Leukaemia x fibroblast hybrid cells augment the antibody response to sheep red blood cells in inbred mice. - Cohen, E P (1985)
ASL-1 x LM(TK-) hybrid cells, an established murine leukaemia x fibroblast hybrid cell line, augment the antibody response to sheep red blood cells in inbred mice, as determined by the plaque assay method. The intraperitoneal injection of viable hybrid cells or of growth medium conditioned by the cells leads to an increase both in the total number as well as the proportion of cells forming antibodies to sheep red blood cells. CSF-1, (M-CSF), is detected by radioimmunoassay in the medium conditioned by the hybrid and LM(TK-) cells, but not ASL-1 parental cells. Prior treatment of the conditioned medium with CSF-1 antiserum reduces its capacity to augment the antibody response, and its proliferative stimulus on cells from the marrow indicating that CSF-1 may be at least partly responsible for the adjuvant effect observed. The intraperitoneal implantation of diffusion chambers containing viable CSF-1 producing hybrid cells, like the cells themselves, also leads to an increase in the number of spleen cells forming antibodies to sheep red blood cells.